2022
DOI: 10.1155/2022/9915247
|View full text |Cite
|
Sign up to set email alerts
|

Manual Compression versus Suture-Mediated Closure Device Technique for VA-ECMO Decannulation

Abstract: Background. The impact of devices for vessel closure on the safety and efficacy of cannula removal in VA-ECMO patients is unknown. Methods. We retrospectively analyzed 180 consecutive patients weaned from VA-ECMO after cardiac arrest or cardiogenic shock from January 2012 to June 2020. In the first period (historical technique group), from January 2012 to December 2018, primary decannulation strategy was manual compression. In the second period (current technique group), from January 2019 to June 2020, decannu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Of these, 22 were excluded due to their focus on veno-arterial ECMO (V-A ECMO) or extracorporeal cardiopulmonary resuscitation (ECPR) [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Fourteen studies were excluded for lack or scarcity of data on CytoSorb© use [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ], four because of the lack of specific data for the ECMO subgroup [ 67 , 68 , 69 , 70 ], four because CytoSorb© was not used concomitantly with ECMO therapy [ 71 , 72 , 73 , 74 ], two because outcomes of interest for the simultaneous use of CytoSorb© and ECMO were not reported [ 75 , 76 ], and one because it focused on a different device [ 77 ]. One study was excluded because it only reported preliminary findings from other articles [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 22 were excluded due to their focus on veno-arterial ECMO (V-A ECMO) or extracorporeal cardiopulmonary resuscitation (ECPR) [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Fourteen studies were excluded for lack or scarcity of data on CytoSorb© use [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ], four because of the lack of specific data for the ECMO subgroup [ 67 , 68 , 69 , 70 ], four because CytoSorb© was not used concomitantly with ECMO therapy [ 71 , 72 , 73 , 74 ], two because outcomes of interest for the simultaneous use of CytoSorb© and ECMO were not reported [ 75 , 76 ], and one because it focused on a different device [ 77 ]. One study was excluded because it only reported preliminary findings from other articles [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…We previously compared manual compression to suture-based closure for VA-ECMO decannulation and showed that femoral compression systems were more frequently used in the manual compression group ( 13 ). Moreover, vascular surgery due to bleeding events were performed numerically more often in the manual compression group compared to the suture-based group (11% vs. 0%) ( 13 ). Combining our previous work with the current data, a plug-based closure device should be the preferred option for save VA-ECMO decannulation to decrease rates of severe bleeding.…”
Section: Discussionmentioning
confidence: 99%